2000
DOI: 10.2170/jjphysiol.50.489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex Steroid Hormones on Substrate Oxidation during Prolonged Submaximal Exercise in Women.

Abstract: Skeletal muscle glycogen is an essential constituent to exercise performance [1]. Several factors are known to affect glycogen storage and utilization within skeletal muscle, such as dietary practices, exercise activity, and hormonal status [1]. Most research concerning this last factor has dealt with traditional metabolic hormones (e.g., epinephrine, insulin, and glucagon). However, so-called non-metabolic hormones also have an impact upon muscle glycogen and thus could affect exercise performance [1]. One su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 14 publications
(17 reference statements)
0
13
0
1
Order By: Relevance
“…Oestrogens may modify muscle strength indirectly by its role in promoting lipolysis, which could modify the amount of fat within the muscle (Wenz et al, 1997;Hackney et al, 2000;Campbell & Febbraio, 2001;D'Eon et al, 2002). In the current trial at the whole body level, although there was no significant change in percent body fat, differences between body weight and LBM indicate that both HRT treated groups likely reduced their absolute body fat from 1 to 1AE5 kg.…”
Section: Groupmentioning
confidence: 60%
See 1 more Smart Citation
“…Oestrogens may modify muscle strength indirectly by its role in promoting lipolysis, which could modify the amount of fat within the muscle (Wenz et al, 1997;Hackney et al, 2000;Campbell & Febbraio, 2001;D'Eon et al, 2002). In the current trial at the whole body level, although there was no significant change in percent body fat, differences between body weight and LBM indicate that both HRT treated groups likely reduced their absolute body fat from 1 to 1AE5 kg.…”
Section: Groupmentioning
confidence: 60%
“…In the current trial at the whole body level, although there was no significant change in percent body fat, differences between body weight and LBM indicate that both HRT treated groups likely reduced their absolute body fat from 1 to 1AE5 kg. Hackney et al (2000) recently reported that combined oestradiol and progesterone administration in women during submaximal exercise enhanced the oxidation of lipid as a substrate and reduced carbohydrate utilization. Hackney et al (2000) recently reported that combined oestradiol and progesterone administration in women during submaximal exercise enhanced the oxidation of lipid as a substrate and reduced carbohydrate utilization.…”
Section: Groupmentioning
confidence: 99%
“…Cadmium can also activate the estrogen receptor alpha (Stoica et al 2000) and, in view of the stimulation of lipid mobilization and lipolysis known to be induced by sex hormones (Hackney et al 2000), this xeno-estrogenic activity might contribute to the negative association with BMI observed for girls, men and women, whereas the fact that cadmium is associated with lower testosterone levels in boys might explain the absence, after adjustment for concurrent exposures, of a significant negative association in boys. That all observed effects were more pronounced at exposure values below the median than at higher exposures, is certainly compatible with a receptor mediated mechanism (see below).…”
Section: Discussionmentioning
confidence: 99%
“…In the boys participating in this study , serum concentrations of marker PCBs showed a positive association with serum levels of endogenous sex hormones. The oestrogenic effects of PCBs might, through stimulation of lipid mobilization and lipolysis known to be caused by sex hormones (Hackney et al 2000), explain the strong negative associations with BMI for both male and female adolescents, and also for female adults. For 26 male adults too a negative association was observed between PCB levels and BMI, that was however only significant after correction for concurrent exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Nos primeiros anos da pós-menopausa há decréscimo da taxa metabólica de repouso (TMR) maior do que na senilidade, provavelmente por conta da diminuição dos hormônios ovarianos. Entre os diversos mecanismos envolvidos destacam-se as mudanças na ação sobre o substrato energético, no repouso e durante o exercício, na regulação do metabolismo de carboidratos e lipídios, e a participação no processo de síntese de proteínas 9 . Há também alterações no consumo, com excesso de ingestão de alimentos energéticos e ingestão elevada de proteínas, associados à deficiência de micronutrientes como as vitaminas A e C, ferro e cálcio 10 .…”
Section: Introductionunclassified